Lipid‐Conjugation of Endogenous Neuropeptides: Improved Biotherapy against Human Pancreatic Cancer. Issue 7 (18th February 2015) - Gopalakrishnan, Gopakumar; Lepetre, Sinda; Maksimenko, Andrei; Mura, Simona; Desmaële, Didier; Couvreur, Patrick
<x xml:space="preserve">Abstract</x> Neuropeptides are small neuronal signaling molecules that act as neuromodulators for a variety of neural functions including analgesia, reproduction, social behavior, learning, and memory. One of the endogenous neuropeptides—Met‐Enkephalin (Met‐Enk), has been shown to display an inhibitory effect on cell proliferation and differentiation. Here, a novel lipid‐modification approach is shown to create a small library of neuropeptides that will allow increased bioavailability and plasma stability after systemic administration. It is demonstrated, on an experimental model of human pancreatic adenocarcinoma, that lipid conjugation of Met‐Enk enhances its tumor suppression efficacy compared to its nonlipidated counterparts, both in vitro and in vivo. More strikingly, the in vivo studies show that a combination therapy with a reduced concentration of Gemcitabine has suppressed the tumor growth considerably even three weeks after the last treatment.